Assessing the impact of the threatened crucian carp (Carassius carassius) on pond invertebrate diversity: A comparison of conventional and molecular tools. Issue 13 (24th October 2020) - Harper, Lynsey R.; Lawson Handley, Lori; Sayer, Carl D.; Read, Daniel S.; Benucci, Marco; Blackman, Rosetta C.; Hill, Matthew J.; Hänfling, Bernd
Abstract: Fishes stocked for recreation and angling can damage freshwater habitats and negatively impact biodiversity. The pond‐associated crucian carp ( Carassius carassius ) is rare across Europe and is stocked for conservation management in England, but its impacts on pond biota are understudied. Freshwater invertebrates contribute substantially to aquatic biodiversity, encompassing many rare and endemic species, but their small size and high abundance complicate their assessment. Practitioners have employed sweep‐netting and kick‐sampling with microscopy (morphotaxonomy), but specimen size/quality and experience can bias identification. DNA and environmental DNA (eDNA) metabarcoding offer alternative means of invertebrate assessment. We compared invertebrate diversity in ponds ( N = 18) with and without crucian carp using morphotaxonomic identification, DNA metabarcoding and eDNA metabarcoding. Five 2 L water samples and 3 min sweep‐net samples were collected at each pond. Inventories produced by morphotaxonomic identification of netted samples, DNA metabarcoding of bulk tissue samples and eDNA metabarcoding of water samples were compared. Alpha diversity was greatest with DNA or eDNA metabarcoding, depending on whether standard or unbiased methods were considered. DNA metabarcoding reflected morphotaxonomic identification, whereas eDNA metabarcoding produced markedly different communities. These complementary tools should be combined for comprehensive invertebrate assessment. Crucian carp presence minimally reduced alpha diversity in ponds, but positively influenced beta diversity through taxon turnover (i.e., ponds with crucian carp contained different invertebrates to fishless ponds). Crucian carp presence contributes to landscape‐scale invertebrate diversity, supporting continued conservation management in England. Our results show that molecular tools can enhance freshwater invertebrate assessment and facilitate development of more accurate and ecologically effective pond management strategies.